Communication and decision-making by central bank committees: different strategies, same effectiveness? - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2005)
The paper assesses the communication strategies of the Federal Reserve, the Bank of England and the European Central Bank and their effectiveness. We find that the effectiveness of communication is not independent from the decisionmaking process in the committee. The paper shows that the Federal Reserve has been pursuing a rather individualistic communication strategy amid a collegial approach to decision-making, while the Bank of England is using a collegial communication strategy and highly individualistic decision-making. The ECB has chosen a collegial approach both in its communication and in its decisionmaking. Assessing these strategies, we find that predictability of policy decisions and the responsiveness of financial markets to communication are equally good for the Federal Reserve and the ECB. This suggests that there may not be a single best approach to designing a central bank communication and decisionmaking strategy.
Keywords: E43; E52; E58; G12; 330; Bank of England; committee; communication; effectiveness; European Central Bank; Federal Reserve; monetary policy; strategies; Kommunikation; Geldpolitik; Entscheidung; Zentralbank; Bewertung; Großbritannien; EU-Staaten; USA